2012
DOI: 10.1080/10962247.2012.699016
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the MOVES2010a, MOBILE6.2, and EMFAC2007 mobile source emission models with on-road traffic tunnel and remote sensing measurements

Abstract: The Desert Research Institute conducted an on-road mobile source emission study at a traffic tunnel in Van Nuys, California, in August 2010 to measure fleet-averaged, fuel-based emission factors. The study also included remote sensing device (RSD) measurements by the University of Denver of 13,000 vehicles near the tunnel. The tunnel and RSD fleet-averaged emission factors were compared in blind fashion with the corresponding modeled factors calculated by ENVIRON International Corporation using U.S. Environmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(70 citation statements)
references
References 16 publications
(23 reference statements)
8
62
0
Order By: Relevance
“…Scaling factors were applied to all emitted chemical species to represent anthropogenic emissions in the year 2013 using the ratio of national annual totals [30]. Recent studies have shown that NO x emissions from sources other than power plants (i.e., mobile sources) in this inventory, which contribute significantly to total NO x emissions, are overestimated and in this study the NEI emission rates are reduced by 50% similar to many recent studies (e.g., [29,[31][32][33][34]). …”
Section: Geos-chem Modelsupporting
confidence: 62%
“…Scaling factors were applied to all emitted chemical species to represent anthropogenic emissions in the year 2013 using the ratio of national annual totals [30]. Recent studies have shown that NO x emissions from sources other than power plants (i.e., mobile sources) in this inventory, which contribute significantly to total NO x emissions, are overestimated and in this study the NEI emission rates are reduced by 50% similar to many recent studies (e.g., [29,[31][32][33][34]). …”
Section: Geos-chem Modelsupporting
confidence: 62%
“…This finding was subsequently supported by SAS observations (Miller et al, 2017). Previous studies had documented such a NOx NEI bias in urban areas (Fujita et al, 2012;Yu et al, 2012; 20 Brioude et al, 2013;Anderson et al, 2014), but our results suggest that the bias is national in extent. After correcting this NOx emission overestimate in GEOS-Chem, we found that we could match the SEAC 4 RS aircraft observations below 1.5 km altitude, but the model mean bias against surface network observations was still 6 ± 14 ppb.…”
supporting
confidence: 45%
“…Some investigators have suggested that mobile source NO x emissions are overestimated after EPA began using MOVES in place of MOBILE6 (see Figure 1). For example, Fujita et al (2012) found that mobile source NO x emissions from the MOVES model overestimated NO x emissions that had been determined from measurements made in a highway tunnel. A fuel-based emission inventory by McDonald et al (2012) yielded relatively constant on-road mobile source NO x emissions from 1990 to 2000 (compared with a 12% reduction in EPA's trend inventory), but comparable (within 7%) mobile source NO x emissions in 1999 and 2008.…”
Section: Precursor Emissionsmentioning
confidence: 99%